The Correlation Between Low Milk Supply in Breastfeeding and The Severity of Neonatal Hyperbilirubinemia - Finanda Nisa Amani; Dianty Anjarsari (The Indonesian Society of Pediatric Gastroenterology, Hepatology, and Nutrition, 2026)
Background: Inadequate breastfeeding can cause neonatal hyperbilirubinemia. Hyperbilirubinemia was the fifth leading cause of neonatal mortality in Indonesia with a prevalence of approximately 5.6%. The severe level of bilirubin concentration can cause life- threatening kernicterus. The study aimed to examine the correlation between low milk supply in breastfeeding and the severity of neonatal hyperbilirubinemia among newborns who were admitted to Assyifa Mother and Child Hospital in Tangerang, Banten. Methods: A cross-sectional study was conducted on 20 neonates diagnosed with unspecified hyperbilirubinemia who were referred to either Emergency Department or Pediatric Department in Assyifa Mother and Child Hospital. Data were obtained from electronic medical records, including information related to mothers and neonates. Data on breast milk supply in breastfeeding mothers were obtained from patient anamnesis records. Statistical analysis was performed using the Fisher’s test with SPSS version 30. Result: Hyperbilirubinemia severity was categorized into three severity levels: level 1 (12-18 mg/dL), level 2 (19-24 mg/dL), level 3 (25-30 mg/dL). There were 8 neonates with adequate breastmilk supply that categorized who were classified into level 2. In contrast, 12 neonates with inadequate breastmilk supply were classified into levels 2 and 3. A significant correlation was found between inadequate breastmilk supply and increased severity of neonatal hyperbilirubinemia (p = 0.042). Higher severity of hyperbilirubinemia was associated with lower quantities of breastfeeding. Conclusion: The study shows a significant correlation between inadequate breastmilk supply in breastfeeding and the severity of neonatal hyperbilirubinemia.